Performances of 18F-FDOPA PET/CT in the Preoperative Evaluation of the Peritoneal Cancer Index in Small Intestine Neuroendocrine Tumors. (21st April 2022) - Morland, David; Jallerat, Pascaline; Brixi, Hedia; Cadiot, Guillaume; Papathanassiou, Dimitri; Deguelte, Sophie
Abstract : Purpose: Peritoneal carcinomatosis (PC) concerns up to 30% of patients with a neuroendocrine tumor (NET), especially of the small intestine. Aggressive management of carcinomatosis seems to be justified, especially with regard to possible mechanical complications. 18 F-FDOPA PET/CT is known to be the most sensitive imaging modality for the detection of small bowel NET metastases, yet its performance in the detection of PC is not well studied. The main objective of our study is to evaluate the performances of preoperative 18 F-FDOPA PET/CT in the prediction of surgical peritoneal cancer index. Methods: All patients referred to our center for an 18 F-FDOPA PET/CT from October 2017 to January 2021 were retrospectively screened. Images were analyzed by a blinded nuclear medicine physician, and peritoneal abnormalities were reported to comply with the surgical peritoneal cancer index standard. Per patient analysis and per region analysis were then conducted. Results: Thirty-three patients were included; 6 patients (35 regions) presented a peritoneal carcinosis. Peritoneal Carcinomatosis Index (PCI) estimated on 18 F-FDOPA PET/CT was significantly and strongly correlated to surgical PCI ( r = 0.96, P < 0.001). Patient-based sensitivity, specificity, negative predictive value, and positive predictive value for 18 F-FDOPA PET/CT were 100%, 93%, 100%, and 75%, respectively. The agreement between 18 F-FDOPA and surgery regarding PC was excellent (Cohen κ = 0.82 on per patient analysis, 0.74 on per region analysis). Conclusions: A preoperative estimation of PCI is achievable based on 18 F-FDOPA PET/CT for small intestine NET and could allow to optimize surgical procedures and patient selection.